Rates of Heat Gain from Occupants of Conditioned Spaces - Gilbert, Jason (McGraw-Hill's AccessEngineering., 2011)
This video uses Tables 12.4.25, 12.4.26, 12.4.27 and 12.4.28 to calculate the internal heat gain from people and equipment.